The millipede genus Antichiropus (Diplopoda: Polydesmida: Paradoxosomatidae), part 3: species of the Pilbara bioregion of Western Australia - Car, Catherine A.; Harvey, Mark S.; Hillyer, Mia J.; Huey, Joel A. (Zootaxa, 2019)
The species of the millipede genus Antichiropus Attems, 1911 found in the Pilbara region of Western Australia are reviewed, and 33 new species are described. The new species are: A. anguinus Car, n. sp., A. antius Car, n. sp., A. apricus Car, n. sp., A. cirratus Car, n. sp., A. confragus Car, n. sp., A. cristatus Car, n. sp., A. cucumeraceous Car, n. sp., A. cunicularis Car, n. sp, A. echinus Car, n. sp., A. filiolus Car, n. sp., A. forcipatus Car, n. sp., A. georginae Car, n. sp., A. gibbus Car, n. sp., A. hystricosus Car, n. sp., A. julianneae Car, n. sp., A. literulus Car, n. sp., A. lucyae Car, n. sp., A. nicholasi Car, n. sp., A. nimbus Car, n. sp., A. patriciae Car, n. sp., A. pendiculus Car, n. sp., A. picus Car, n. sp., A. procerus Car, n. sp., A. quaestionis Car, n. sp., A. rupinus Car, n. sp., A. salutus Car, n. sp., A. servulus Car, n. sp., A. simmonsi Car, n. sp., A. sloanae Car, n. sp., A. spathion Car, n. sp., A. uvulus Car, n. sp., A. verutus Car, n. sp. and A. vindicatus Car, n. sp.. The number of described Antichiropus species now stands at 72. Two species (A. julianneae Car, n. sp. and A. pendiculus Car, n. sp.) lack one diagnostic feature of the genus, namely a solenomere process, but are included here because they conform to the genus definition in all other characters. We also obtained sequence data from four mitochondrial genes (cytochrome c oxidase subunit 1 [COI], cytochrome c oxidase subunit 3 [COIII], cytochrome B [CytB], and 12S rRNA [12S]), and one nuclear gene (28S rRNA [28S]) for 19 species. Three main clades were recovered: one in the northern Pilbara, one in the southern Pilbara, and one just outside the south-western margin of the Pilbara.